1979
DOI: 10.1007/bf00406579
|View full text |Cite
|
Sign up to set email alerts
|

The presence and significance of the Thomsen-Friedenreich antigen in mammary gland

Abstract: Normal tissue as well as various benign and malignant lesions of the breast were histochemically examined for the presence of the Thomsen-Friedenreich (TF)-antigen. Fluorescein- or 3H-labelled peanut agglutinin was used for this purpose, a lectin that is known to have a high affinity for the TF-antigen. The occurrence of this TF-antigen seemed in all cases, even in the carcinoma lobulare in situ that is regarded as being derived from myoepithelial cells by some authors, to be associated with a secretory condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…In normal human tissues the T antigen can be unmasked by desialylation in the urinary bladder (Coon et al, 1982), but such treatment has only a limited effect, or no effect at all, in breast and colon mucosa (Klein et al, 1979;Yuan et al, 1986). In spite of this difference in normal tissues, carcinomas of bladder, breast and colon have been reported to express T (Coon et al, 1982;Limas and Lange, 1986;Klein etal., 1979;Yuan et al, 1986) and Tn antigens (Longenecker et al, 1987).…”
Section: -Linked Mucin-type Glycoproteins In Normal and Malignant Comentioning
confidence: 99%
See 1 more Smart Citation
“…In normal human tissues the T antigen can be unmasked by desialylation in the urinary bladder (Coon et al, 1982), but such treatment has only a limited effect, or no effect at all, in breast and colon mucosa (Klein et al, 1979;Yuan et al, 1986). In spite of this difference in normal tissues, carcinomas of bladder, breast and colon have been reported to express T (Coon et al, 1982;Limas and Lange, 1986;Klein etal., 1979;Yuan et al, 1986) and Tn antigens (Longenecker et al, 1987).…”
Section: -Linked Mucin-type Glycoproteins In Normal and Malignant Comentioning
confidence: 99%
“…The findings indicate that different carbohydrate structures carry T and Tn structures as internal cryptic antigens in bladder and colon and, consequently, that the mechanisms leading to their unmasking in carcinomas vary from one tissue to another tissue. Previous immunohistological studies of T antigens have been performed with PNA lectin (Coon et al, 1982;Limas and Lange, 1986;Langkilde et al, 1989;Klein et al, 1979;Yuan et al, 1986;0rntoft et al, 1985), with sera containing polyclonal anti-T antibodies (Yuan et al, 1986;0rntoft et al, 1985;Springer et al, 1985), and with anti-T MAbs (Yuan et al, 1986;Itzkowitz et al, 1989). However, results obtained on tissue sections as well as in a cell binding assay (Wolf et al, 1986) indicate a general heterogeneity in specificity of reagents, in tumor-binding capacity, and in the molecules which express the binding sites.…”
Section: -Linked Mucin-type Glycoproteins In Normal and Malignant Comentioning
confidence: 99%
“…A wide variety of other lectins have been investigated (139) to determine their usefulness in breast cancer prognosis, with conflicting results. For instance, whereas Furmanski et al (140) found binding to correlate with early recurrence, others have found binding to correlate with higher levels of differentiation (141,142).…”
Section: Biochemical Markers In Tumor Tissuementioning
confidence: 94%
“…Das Mammakarzinom ist z.B. durch eine verstärkte PNA-Bindung an die Zell membran der gut differenzierten Karzinome charakteri sierbar, während das normale Gewebe und das entdifferenzierte Karzinomgewebe signifikant geringere PNALektinbindungen aufwiesen [14,15]. Eine hormonab hängige PNA-Bindung wird auch beim differenzierten Prostatakarzinom angenommen, da dieses Gewebe sich am intensivsten anfärben liess [9], Beim Hodenkarzinom fehlen Untersuchungen über die Androgenrezeptorenkonzentrationen, so dass keine Rückschlüsse auf einen vergleichbaren pathophysiologischen Mechanismus möglich sind.…”
Section: Materialien Und Methodikunclassified